Physical fitness for health - Susumu S. Sawada (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Physical factors for health include cardiorespiratory fitness (CRF), muscle fitness/endurance, body composition, and flexibility. Many epidemiological studies have reported the relationship between CRF and health. A representative cohort study regarding CRF, the Aerobics Center Longitudinal Study was published. Also, cohort studies involving Japanese people, the Tokyo Gas Study, Juntendo University alumni study, and Japan Epidemiology Collaboration on Occupational Health study have been presented. Most of these studies indicated that all-cause mortality and cancer mortality were low in persons in whom high-level CRF was maintained, and that the incidences of hypertension and diabetes were low in these persons as well. These results suggest that premature death and some lifestyle-related diseases can be prevented by maintaining a high-level of CRF, that is, by continuously performing active physical activity.